Nonclassical Vitamin D Action - Zittermann, Armin (Molecular Diversity Preservation International, 2010)
It is becoming increasingly clear that vitamin D has a broad range of actions in the human body. Besides its well-known effects on calcium/phosphate homeostasis, vitamin D influences muscle function, cardiovascular homeostasis, nervous function, and the immune response. Vitamin D deficiency/insufficiency has been associated with muscle weakness and a high incidence of various chronic diseases such as cardiovascular disease, cancer, multiple sclerosis, and type 1 and 2 diabetes. Most importantly, low vitamin D status has been found to be an independent predictor of all-cause mortality. Several recent randomized controlled trials support the assumption that vitamin D can improve muscle strength, glucose homeostasis, and cardiovascular risk markers. In addition, vitamin D may reduce cancer incidence and elevated blood pressure. Since the prevalence of vitamin D deficiency/insufficiency is high throughout the world, there is a need to improve vitamin D status in the general adult population. However, the currently recommended daily vitamin D intake of 5-15 µg is too low to achieve an adequate vitamin D status in individuals with only modest skin synthesis. Thus, there is a need to recommend a vitamin D intake that is effective for achieving adequate circulating 25-hydroxyvitamin D concentrations (>75 nmol/L).